Diet and risk for hernia: a Mendelian randomization analysis - Yang, Yanjiang; Han, Biao; Yang, Wenwen (Frontiers in Nutrition, 2024)
Background: The relationship between dietary factors and hernias is currently unclear.Methods: The UK Biobank was used to extract dietary factors that were used as exposures, including intake of alcohol, non-oily fish, beef, fresh fruit, oily fish, salad/raw vegetables, dried fruit, coffee, cereal, salt, tea, water, cooked vegetables, cheese, Lamb/mutton, pork, poultry, processed meat, and bread. The FinnGen biobank was used to obtain GWAS data on hernias as outcomes. The main analysis of this study was performed using the weighted median, MR-Egger, and IVW methods. Cochran's Q test was utilized to assess heterogeneity. To find potential outliers, the MR-PRESSO method was used. Leave-one-out analysis was employed to assess the IVW method's robustness.Results: Alcoholic consumption per week (OR: 0.614; p= 0.00614) reduced the risk of inguinal hernia. Alcohol intake frequency (OR: 1.309; p= 0.0477) increased the risk of ventral hernia (mainly including incisional hernia and parastomal hernia). The intake of non-oily fish (OR: 2.945; p= 0.0214) increased the risk of inguinal hernia. Salt added to food (OR: 1.841; p= 0.00267) increased the risk of umbilical hernia. Cheese intake (OR: 0.434; p= 0.000536) and dried fruit intake (OR: 0.322; p= 0.00716) decreased the risk of ventral hernia, while cooked vegetable intake (OR: 4.475; p= 0.0380) increased the risk of ventral hernia. No causal relationships were found with hernias from other dietary factors.Conclusion: Inguinal, umbilical, and ventral hernias are all related to dietary factors.